Calon Tunggal dalam Pilkada Serentak Tahun 2015 terhadap Putusan Mahkamah Konstitusi No 100/PUU-XIII/2015 - Nazriyah, R. (Jurnal Konstitusi, 2016)
The phenomenon of a pair-single candidate threatens delays in the implementation of simultaneous Regional Head Elections in some districts until 2017. Although the Commission extends the registration period of candidates to avoid the delay of elections simultaneously, there are still some districts that have a single candidate. The law on elections has not set the provisions definitely regarding what should be done if there is the phenomenon of a single candidate. Finally the parties who feel aggrieved the rights had filed a judicial election law to the Constitutional Court (MK) to find solutions to these issues. In its decision, the Court considered that the Act mandates the election as the executor of the sovereignty of the people to elect regional heads directly and democratically. Thus, the local elections should ensure the realization of the highest power in the hands of the people. In addition, the Court also considers the formulation of norms of Law No. 8 of 2015, which requires the presence of more than one pair of candidates does not provide a solution, which led to the legal vacuum. This can result in absent of holding the elections. Local elections which are only followed by a single pair of candidates, the mechanism selection is to determine whether the “Agree”  or “Disagree” with   the prospective partner. If it turns out the people’s voice is more to select “Agree” then the candidate is designated as regional head and deputy head of the selected district. Conversely, if it turns out the people’s voice is more to select “Disagree” then in such circumstances the election is postponed until the next local elections simultaneously.